Kia Ora, Fairy Tale - Kayes, Anne Margaret (Auckland University of Technology, 2014)
The Tui Street Tales is a collection of stories for children aged approximately nine to twelve years. The stories take place in Tui Street, where two boys realise that fairy tale themes are running through the mysteries occurring in their street. They, along with other Tui Street children, set out to solve these mysteries. Contemporary issues facing children today are explored, such as divorce, cyberbullying, parental death and environmental pollution. Archetypal expectations are often subverted, as characters forge their own paths. The New Zealand setting is often a character itself and influences events and characters. The exegesis accompanying this thesis explores how the European fairy tale has both influenced and been influenced by society and culture throughout history. It explores how, over the last fifty years in particular, writers have re-written fairy tales not only as a vehicle for social change, but to restore them to something more like their original selves. It also explores how elements of the traditional fairy tale have appeared and might yet appear in a modern New Zealand context. This research both enriched and informed the process of writing The Tui Street Tales.
Keywords: Children's stories; New Zealand children's literature; Fairy tales